Exploring the Operationalization of Intersectionality in Political Science – A Scoping Review Protocol - Habtegergesa, Makda (Peer Beyond Graduate Research Conference, 2025)
Intersectionality has become an increasingly salient analytical framework in political science, offering a critical lens to examine the interwoven nature of social categorizations and their implications for political representation and policymaking. Despite its widespread theoretical adoption, the discipline lacks a unified methodological approach to its empirical application. This scoping review protocol presents a systematic strategy to map the existing literature, critically assess prevailing definitions, methodologies, and measurement strategies, and identify conceptual and empirical gaps.